2008
DOI: 10.1093/deafed/enn014
|View full text |Cite
|
Sign up to set email alerts
|

Learning via Direct and Mediated Instruction by Deaf Students

Abstract: Four experiments investigated classroom learning by deaf college students receiving lectures from instructors signing for themselves or using interpreters. Deaf students' prior content knowledge, scores on postlecture assessments of content learning, and gain scores were compared to those of hearing classmates. Consistent with prior research, deaf students, on average, came into and left the classroom with less content knowledge than hearing peers, and use of simultaneous communication (sign and speech togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 15 publications
3
29
0
3
Order By: Relevance
“…More recent studies, however, have indicated that experienced teachers of the deaf signing for themselves do not facilitate learning to any greater extent than when they use sign language interpreters, regardless of whether the teachers are hearing or deaf [55].…”
Section: Discussionmentioning
confidence: 94%
“…More recent studies, however, have indicated that experienced teachers of the deaf signing for themselves do not facilitate learning to any greater extent than when they use sign language interpreters, regardless of whether the teachers are hearing or deaf [55].…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, in a series of following experiments, the authors aimed to understand the extent to which interpreting provides deaf students with true access to education by comparing direct (instructor uses ASL) and mediated instructions (via ASL interpreter) [15]. Results showed that direct and mediated instructions can be equally effective; however, the quality of instruction for deaf students is more important than mode of communication per se; that is, when the class is well designed, there is no learning "gap".…”
Section: Learning and Deafnessmentioning
confidence: 99%
“…Despite more than 40 years of research on the challenges that DHH students face in classrooms [13,15,26], there is little work done by cognitive scientists on potential solutions or guidelines to solve these issues, which include students not being able to attend to two different sources of visual information, classroom pacing, interpreters not being fully qualified, and interpreters being confronted by multiple conversations and interruptions,.…”
Section: Learning and Deafnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying reason is that the classrooms are not designed to utilize students' visual skills and are not fully accessible by DHH students, including engineering classrooms 6 . When teachers maximize the benefits of visual learning, the barriers in regular lectures for DHH students, such as using spoken English is partially ameliorated 7 . Hearing students are able to simultaneously watch the visuals and listen to the spoken explanation, while DHH students have to choose either the visuals or captions.…”
Section: Challengesmentioning
confidence: 99%